Edukasi Tentang Manfaat Terapi Komplementer Pada Ibu Nifas - Ariu Dewi Yanti, Ariu Dewi Yanti; Siti, Siti Indatul Laily; Firda Muflikhatul I; Eka Fauziah R (Universitas Merdeka Surabaya, 2023)
Problems that often occur in postpartum mothers are starting from worry and anxiety in facing childbirth, having a good role as a mother, feeling laceration pain due to childbirth (both normal and SC), feeling tired, and experiencing sleep disturbances which result in inhibited or not milk production. fluent. Then the solution that can be done in overcoming the above problems is by pharmacological and non-pharmacological ways. One of the non-pharmacological ways is to apply complementary therapy. The targets in community service activities are all postpartum mothers in the PMB Ny. Rindra Deviasti, SST., M.KM. The purpose of providing education about complementary therapy is to increase mother's knowledge about the benefits of complementary therapy and provide a sense of relaxation and can reduce anxiety in postpartum mothers. In community service activities, the servant wants to provide education about the benefits of complementary midwifery therapy. Out of 20 respondents, 16 (80%) postpartum mothers did not understand and did not know about the benefits of complementary therapy for postpartum mothers. After being given education about complementary therapy, all postpartum mothers understood the benefits of complementary therapy. After that, postpartum women were given a questionnaire again after being given education. The result was that as many as 20 respondents (100%) already understood the benefits of complementary therapy. Based on the implementation of this service program, there was a change in the knowledge of postpartum mothers about the benefits of complementary therapy, especially for postpartum mothers. With community service activities, it is hoped that it can increase the knowledge of postpartum mothers and be able to overcome problems that often occur, especially anxiety faced during the postpartum period.